The Application of Total Physical Response (TPR) Method in English Basic Learning for Early Children in TK/KB Al-Ikhlas Tenggilis-Surabaya - Sumiati; Kinanti Resmi Hayati (Future Science)
Foreign languages learning, especially English is needed to face 4.0 revolution industries. Everything related to technology always uses English as its main language. Therefore, English should be introduced since early to optimize English ability. One of the problems for Indonesian people in learning English is the English position that usually known as a foreign language. This should be one of the biggest things that must be considered by the Indonesia Government to be able to communicate whether with the international or technology world. The introduction and learning of English from an early age can overcome difficulties in understanding and using foreign languages in everyday life. Total Physical Response (TPR) Method application in English Learning are one of the most appropriate and effective for being applied in teaching and learning process in the classroom for the level of Early Childhood Education (PAUD) or Kindergarten (TK) especially for TK / KB Islam Al-Ikhlas Tenggilis - Surabaya as one of the pilot Islamic kindergartens in Surabaya